(untitled) (Web of Teachers: Inderscience Research, 2026)
This article examines the influence of Babur’s Baburnama on English literary perception of the East. Through critical analysis of its English translations—Beveridge (1922), Leyden-Erskine (1826), and Thackston (1996)—the study explores how the text shaped Western understanding of Eastern identity and self-representation. The article argues that the Baburnama fundamentally challenged Orientalist stereotypes by presenting a multifaceted, humanized portrait of an Eastern ruler whose introspection and literary sensibility defied Western expectations. Drawing on reception history and postcolonial critique, the analysis reveals how the text contributed to reconfiguring English literary perceptions toward more nuanced understandings of Eastern subjectivity.